Unveiling the Impact of Cultural Value Orientations on Ideation Outcomes: Evidence From the International #EUvsVirus Hackathon - Benjamin P. Krebs; Marieke Funck; Slawa Tomin; Bernhard Wach; Rüdiger Kabst (R&D Management, 2025)
This study addresses the role of national culture in shaping hackathon teams' ideation outcomes. Drawing on the innovation and creativity literature and Schwartz' theory of cultural value orientations, we propose that hierarchical values decrease the quality of ideas that teams develop over the course of a hackathon and that intellectual autonomy and mastery improve it. Using archival data, including pitch presentations from an international hackathon and data on cultural value orientations, we compiled a sample of 308 teams to investigate the influence of cultural value orientations and employed linear mixed-effects regression analysis to test our hypotheses. We found that hierarchical cultural values are negatively associated with the quality of ideas, which suggests that hackathon teams that operate in such cultures suffer from a “liability of hierarchy.” We also found that teams from societies that emphasize mastery of the natural and social environment are more likely than other teams are to develop high-quality ideas to tackle the (grand) challenges that hackathons address. We found no relationship between intellectual autonomy and idea quality. The study findings support the notion that culture manifests in hackathon teams' behavior and so shapes the quality of ideas they develop, thus laying the foundation for success or failure.
Keywords: 650; creativity; hackathon teams; idea quality; innovation; national culture